PENGARUH VARIASI TIME REPETITION (TR) TERHADAP KUALITAS CITRADAN INFORMASI CITRA PADA PEMERIKSAAN MRI LUMBALSEKUENS T2 FSE POTONGAN SAGITAL - Syafrudin Nizar; Fatimah Fatimah; Irwan Kartili (Poltekkes Kemenkes Semarang, 2019)
Background : TR (Time Repetition) is an MRI parameter. TR controls the amount of longitudinal magnetization recovery before the next RF pulse. TR parameter is one of parameters that can affect image quality and image information. Long TR arrangements can increase SNR (Signal To Noise Ratio), CNR (Contrast To Noise Ratio) and provide better contrast, but increase the examination time. The purpose of this research is to know the effect of TR to image quality, difference of image information and TR optimal on MRI Lumbal sequence T2 FSE sagittal.Methods : The type of this research is quantitative research with experimental approach. The sample of research used is 6 probandus. TR variations used are TR 2000, 2500, 3000, 3500, 4000 with other parameters controlled. Aspects of image quality and image information values assessed in this study include Corpus Vertebrae, Discus Vertebrae, Cerebro Spinal Fluid (CSF), Medulla Spinalis, and Soft Tissue. Processing and analysis of image quality data is done by data normality test using shapiro-wilk, then test influence correlation pearson, linear regression and repeated anova. and for image information is done normality data test using shapiro-wilk, and friedman test.Result : The results of the test analysis showed that there was a TR effect on SNR image quality (p = 0.001) and CNR (p = 0.007) with (p 0.05) on all assessed organs. There is a difference in image information of MRI Lumbal T2 FSE sequence of sagittal pieces on Time Repetition variation with significance value (p 0.05). The optimal TR value on image quality is found on TR 4000 variation with mean of highest mean rank that is 42.82. While the optimal TR value on the image information is on the variation of TR 3000 with the highest mean mean rank is 3.25. TR 3000 is considered to produce better image information and is considered optimal on MRI Lumbal sequences of T2 FSE sagittal fragments compared to other TR variations with a duration of examination time of 2 minutes 30 seconds.Conclusion: Based on the results that good variation TR used on MRI Lumbal examination sequence T2 FSE sagital view is TR 3000 with best image qualit, informative image information and short scanning time.